O comportamento empreendedor no mercado informal - Soares, Evelyn Frazão (2014)
This study was developed with the objective to analyze the relationship between entrepreneurial competencies and entrepreneurial behavioral characteristics of owners of stalls in Popular Malls segment. The methodology is based on the quantitative approach, the exploratory and theory-based empirical research. The participants in this study totaled 220 owners of stalls in popular malls segment, 116 of these belong to the Popular Shopping in São Luis / MA 104 and the Popular Shopping in Natal / RN. The data collection instrument consisted of three questionnaires, and in order to facilitate the implementation, they were organized through blocks, namely: (I) Characterization of the profile; (II) Entrepreneurial Skills (BRANDÃO, 2007) and (III) Behavioral Characteristics Entrepreneurs (MCCLELLAND, 1961). Data were analyzed using descriptive statistics, nonparametric tests and correlations. It was evidenced by the general characterization of the profile the predominance of males (54.34%), aged 34-41 years (28.64%), married (50.45%), with pay between 1-3 wages minimum (40.91%), with secondary education (61.36%) having 1-3 children (60.45%) and lack firm (86.36%). Overall we identified average levels of Entrepreneurial Competencies (41.82%) and Behavioral Characteristics of Entrepreneurs (74.09%). Noteworthy is the average level of strategic action (56.48%) and the high level of achievement (68.18%). When compared, entrepreneurs São Luis / MA (17.24%) have a higher level of competence view of the environment than the entrepreneurs of Natal / RN (16.35%). In turn, entrepreneurs of Natal / RN (58.65%) have a higher level of attainment characteristic of entrepreneurs São Luis / MA (49.14%). The correlations were generally positive and weak for the size of Entrepreneurial Competencies with Behavioral Characteristics of Entrepreneurial dimensions, except for a moderate positive correlation dimension for strategic action planning with the size. Among Entrepreneurial Skills and Behavioral Characteristics Entrepreneurs constructs, the correlation was positive and demonstrated weak. The results obtained allow us to state the presence of such constructs in respondents, be they owners of stalls in Popular Malls segment as well as allow us to assert the existence of a correlation between the skills and characteristics, however it proved weak. Therefore it is expected that the completion of this study will serve as a reflection for researchers of entrepreneurial behavior, resulting in improvements in policy and / or programs and actions aimed at supporting the development of entrepreneurial activity in the regions.